2016
DOI: 10.1002/ar.23470
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Vomeronasal System From an Integrated Perspective

Abstract: "Olfactory subsystems" is a relatively new terminology to refer to the different regions of the nasal cavity featuring olfactory sensory neurons. In mice, the olfactory chemical cues are detected in four well delimited areas: the main olfactory epithelium, the septal organ, Grüneberg's ganglion, and the sensory epithelium of the vomeronasal organ. Nevertheless, such distribution is by no means exhibited by all mammals. In microsmatic mammals -humans included- the only existing olfactory subsystem is the main o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…It has been suggested that it may have disappeared in many mammals and could be suffering a phylogenetic regression in others. It has not been identified either in cats, pigs, sheeps or dogs (Barrios et al, ; Salazar et al, ).…”
Section: The Olfactory Nerve Contains Axons From Different “Olfactorymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that it may have disappeared in many mammals and could be suffering a phylogenetic regression in others. It has not been identified either in cats, pigs, sheeps or dogs (Barrios et al, ; Salazar et al, ).…”
Section: The Olfactory Nerve Contains Axons From Different “Olfactorymentioning
confidence: 99%
“…It has been proposed that the Grüneberg's ganglion can be involved in innate and/or social inter‐individual interactions, but the specific roles that it can play still remain elusive. From a comparative perspective, the Grüneberg's ganglion has only been identified in adult mice and rats (Gruneberg, ), but not in domestic mammals (Salazar et al, ). In fact, it has been suggested that Grüneberg's ganglion can be a structure in regression during development (Gruneberg, ; Salazar et al, ).…”
Section: The Olfactory Nerve Contains Axons From Different “Olfactorymentioning
confidence: 99%
“…Thus, each species should be studied independently, so as to avoid extrapolating information from the published data (Salazar et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this general description, each species has its own unique characteristics, not only anatomic but also related to G-protein expression and vomeronasal receptor families. Thus, each species should be studied independently, so as to avoid extrapolating information from the published data (Salazar et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The vomeronasal organ (VNO) is mentioned in the chapter Respiratory system, in the part concerning the histological description of the nasal cavity. The VNO is a specialized organ, which forms an integral supportive part of the olfaction of many animal species for example in brown bear (Tomiyasu et al 2017), horse (Lee et al 2016), giraffe (Kondoh et al 2017), or even in mouse (Aland et al 2016;Salazar et al 2016) and reptiles (Mangiacotti et al 2019). It is believed that the main function of vomeronasal organ is to regulate various behavioral aspects of intraspecies interaction by facilitating the detection of pheromones.…”
Section: Vomeronasal Organmentioning
confidence: 99%